The cellular thermal shift assay : a novel biophysical assay for in situ drug target engagement and mechanistic biomarker studies - Martinez Molina, Daniel (2018)
A drug must engage its intended target to achieve its therapeutic effect. However, conclusively measuring target engagement (TE) in situ is challenging. This complicates preclinical development and is considered a key factor in the high rate of attrition in clinical trials. Here, we discuss a recently developed, label-free, biophysical assay, the cellular thermal shift assay (CETSA), which facilitates the direct assessment of TE in cells and tissues at various stages of drug development. CETSA also reveals biochemical events downstream of drug binding and therefore provides a promising means of establishing mechanistic biomarkers. The implementation of proteome-wide CETSA using quantitative mass spectrometry represents a novel strategy for defining off-target toxicity and polypharmacology and for identifying downstream mechanistic biomarkers. The first year of CETSA applications in the literature has focused on TE studies in cell culture systems and has confirmed the broad applicability of CETSA to many different target families. The next phase of CETSA applications will likely encompass comprehensive animal and patient studies, and CETSA will likely serve as a very valuable tool in many stages of preclinical and clinical drug development.